The Efficiency of Beef Cattle Production in the Target Area of Concentration, Johor - Serin, Tapsir (2004)
The production of beef in Malaysia is inadequate to meet the demand, due to the rapid increase in consumption and population. The Target Area Concentration (TAC) project is expected to be a major contributor to boost beef cattle production. This study examines the efficiency of resources used in the beef cattle production in the TAC in Johor, Malaysia. It addresses the issues on productivity and technical efficiency of beef cattle operations and their relationship with management inventory, farm performances, animal husbandry practices, as well as socio economic and demographic factors. The translog and Cobb-Douglas stochastic frontier production functions were used to examine the issues of technical efficiency in the TAC project. The frontier regression model was estimated using the maximum likelihood estimation (MLE) technique. The translog stochastic frontier model was found to be suitable in representing the sample data and provide better estimates than the Cobb-Douglas model. iv The results indicated that the beef operation in the TAC has an increasing return to scale. The average computed technical efficiency for individual farm units is 0.6829. The majority of the farms (51%) were between 40% to 80% of technical efficiency. The total loss in production due to inefficiency was estimated about 3,094 heads of beef cattle in Animal Unit (AU) per year. The study also found that there was a significant different in average technical efficiency by TAC location. However, the technical efficiency was not significantly different by farm types, ownership, and sizes. The findings of this study suggest that there is room for expansion, through the adoption of best practice technology and optimal resource allocation. The farm’s technical efficiency could be improved by better planning and controlling skills by the farmers/managers, longer experience, proper training, more frequent of advisory services by extension agents, higher calving rate, involvement by DVS in breeding and health management services and by using cross breed cattle